The visible hand: Finger ratio (2D:4D) and competitive behavior - Matthew Pearson; Burkhard C. Schipper (University of California, Department of Economics, 2009)
In an experiment using two-bidder first-price sealed bid auctions with symmetric independent private values, we scan also the right hand of each subject. We study how the ratio of the length of the index and ring fingers (2D:4D) of the right hand, a measure of prenatal hormone exposure, is correlated with bidding behavior and total profits. 2D:4D has been reported to predict competitiveness in sports competition (Manning and Taylor, 2001, and Honekopp, Manning and Muller, 2006), risk aversion in an investment task (Dreber and Hofman, 2007), and the average profitability of high-frequency traders in financial markets (Coates, Gurnell and Rustichini, 2009). We do not find any significant correlation between 2D:4D and both bidding or profits. Yet, our study raises an issue of ethnic differences with respect to 2D:4D.
Keywords: C72; C91; C92; D44; D81; D87; 330; hormones; digit ratio; 2D:4D; risk behavior; competition; competitive behavior; bidding; endocrinological economics